γ-Tocotrienol Ameliorates Intestinal Radiation Injury and Reduces Vascular Oxidative Stress after Total-Body Irradiation by an HMG-CoA Reductase-Dependent Mechanism - Berbée, Maaike (2009)
Analogs of vitamin E (tocols) are under development as radioprophylactic agents because of their high efficacy and lack of toxicity. Gamma-tocotrienol (GT3) is of particular interest because, in addition to being an antioxidant, it also inhibits 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase and accumulates to greater extent in endothelial cells than other tocols. We addressed in vivo whether HMG-CoA reductase inhibition contributes to the radioprotection conferred by GT3. Groups of mice were treated with vehicle, mevalonate (the product of the reaction catalyzed by HMG-CoA reductase), GT3 alone or GT3 in combination with mevalonate. Lethality and standard parameters of injury to the hematopoietic, intestinal and vascular/endothelial systems were assessed after exposure to total-body irradiation. GT3 improved post-irradiation survival and decreased radiation-induced vascular oxidative stress, an effect that was reversible by mevalonate. GT3 also enhanced hematopoietic recovery, reduced intestinal radiation injury, and accelerated the recovery of soluble markers of endothelial function. These parameters were not reversed by mevalonate co-administration. Our data confirm GT3’s radioprophylactic properties against hematopoietic injury and, for the first time, demonstrate benefits in terms of protection against gastrointestinal and vascular injury. The radioprotective efficacy of GT3 against vascular injury is related to its properties as an HMG-CoA reductase inhibitor.